2006
DOI: 10.1021/es0604461
|View full text |Cite
|
Sign up to set email alerts
|

Ettringite-Induced Heave in Chromite Ore Processing Residue (COPR) upon Ferrous Sulfate Treatment

Abstract: A pilot-scale treatment study was implemented at a deposition site of chromite ore processing residue (COPR) in New Jersey. Ferrous sulfate heptahydrate (FeSO4 x 7H2O) was employed to reduce hexavalent chromium in two dosages with three types of soil mixing equipment. XANES analyses of treated samples cured for 240 days indicated that all treatment combinations failed to meet the Cr(VI) regulatory limit of 240 mg/kg. More importantly, the discrepancy between XANES and alkaline digestion results renders the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 14 publications
(21 reference statements)
7
63
0
Order By: Relevance
“…The difference in Cr(VI) percentage obtained with alkaline digestion (16%) and XANES (34%) suggests that the alkaline digestion may underestimate the Cr(VI) content. The observation was in agreement with recent reports comparing the alkaline digestion and XANES analysis [26,27]. Therefore, the Cr(VI) content determined with XANES (19 490 mg kg −1 ) was used in the following bioaccessibility calculations.…”
Section: Copr Characterizationsupporting
confidence: 89%
“…The difference in Cr(VI) percentage obtained with alkaline digestion (16%) and XANES (34%) suggests that the alkaline digestion may underestimate the Cr(VI) content. The observation was in agreement with recent reports comparing the alkaline digestion and XANES analysis [26,27]. Therefore, the Cr(VI) content determined with XANES (19 490 mg kg −1 ) was used in the following bioaccessibility calculations.…”
Section: Copr Characterizationsupporting
confidence: 89%
“…In a previous study, ettringite induced swelling was observed upon ferrous sulfate treatments (Dermatas et al 2006b;Moon et al 2007). However, the effects of lithification and initial dry density under unconfined swell conditions were not investigated.…”
Section: Introductionmentioning
confidence: 85%
“…The ferrous sulfate was applied to the ground surface and then mixed into the COPR using the rotating drum. The detailed mixing process has been explained in a previous publication (Dermatas et al 2006b). …”
Section: Experimental Methodologymentioning
confidence: 99%
“…A lawsuit was enacted against the owner of a 34-acre site (denoted as SA7) on the Hackensack river in Jersey City, NJ, leading to the digging and hauling of 1.5 million tons of COPR. The site owner sought an alternative solution and initiated an extensive remedial investigation (Dermatas et al, 2006a and2006b). …”
Section: Introductionmentioning
confidence: 99%